Diachronous Increase in Early Cambrian Ichnofossil Size and Benthic Faunal Activity in Different Climatic Regions. (March 2014) - Mochizuki, Takafumi; Oji, Tatsuo; Zhao, Yuanlong; Peng, Jin; Yang, Xinglian; Gonchigdorj, Sersmaa
Abstract : In order to clarify the pattern of diversification and processes of biological activity during the Cambrian radiation, ichnofossils were comparatively studied in the early Cambrian sections of Newfoundland, South China and western Mongolia. Special attention was paid to size distributions of the most common ichnogenus, Planolites, and the densities of all the observed ichnofossils that preserve animal activity as expressed by bedding plane bioturbation indices (BPBI). From the Fortune Head section in Newfoundland, a clear size increase in the ichnogenus Planolites is confirmed from the Treptichnus pedum Zone to the overlying Rusophycus avalonensis Zone. The BPBI also shows much stronger biological activity in the R. avalonensis Zone than in the T. pedum Zone. In Meishucun, South China and Gobi-Altai, Mongolia, however, a variety of Planolites sizes had already appeared in the T. pedum Zone, and the BPBI's on some bedding surfaces of the T. pedum Zone are already comparable to those in the R. avalonensis Zone in Newfoundland. In the earliest Cambrian, diversification and increase in the biological activity of the benthic fauna were diachronous in the wide geographic scale, starting earlier at lower latitudes (South China and western Mongolia) than at higher latitudes (Newfoundland), reflecting differences in the onset of Cambrian benthic animal activity under different climatic conditions.